2019
DOI: 10.1159/000500542
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Heroin and Cocaine Use among Opioid-Dependent Patients during Methadone, Buprenorphine or Morphine Opioid Agonist Therapy

Abstract: Background: Among all the treatment methods developed so far, opioid agonist treatment (OAT) is the most effective therapy for opioid dependence. While methadone (MTD) is the most commonly used, fewer data are available on alternative opioid agonist. The aim of this study was to assess the efficacy of buprenorphine (BUP) and slow-released morphine compared to MTD with regard to the reduction of concomitant heroin and cocaine use. Methods: This cross-sectional study included 105 patients receiving MTD, BUP, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The systematic review by Mattick et al [21] demonstrated the efficacy of buprenorphine maintenance treatment, with a lower retention rate than methadone but allowing a similar decrease in opiate consumption. Some recent data suggest that buprenorphine maintenance treatment is associated with reduced additional opiate couse comparing with methadone or slow-release morphine maintenance treatment [22]. In addition, buprenorphine has been shown to reduce heroin overdose [23,24], and some data suggest that the death rate is lower for patients maintained by buprenorphine compared to patients maintained by methadone [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Mattick et al [21] demonstrated the efficacy of buprenorphine maintenance treatment, with a lower retention rate than methadone but allowing a similar decrease in opiate consumption. Some recent data suggest that buprenorphine maintenance treatment is associated with reduced additional opiate couse comparing with methadone or slow-release morphine maintenance treatment [22]. In addition, buprenorphine has been shown to reduce heroin overdose [23,24], and some data suggest that the death rate is lower for patients maintained by buprenorphine compared to patients maintained by methadone [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Hair samples were originally analyzed in the context of a study conducted in an outpatient setting at the Centre for Addictive Disorders of the Psychiatric Hospital, University of Zurich in 2014. 22,23 From that study, we analyzed in further detail a range of substances in 104 patients, including 76 male and 28 female participants, in opioid substitution therapy. All 104 patients were included in this cross-sectional study, including 12 with comorbid dextromethorphan use and 92 patients with no dextromethorphan use.…”
Section: Subjectsmentioning
confidence: 99%
“…Assuming an average growth rate of 1 cm/month, the hair segment represents the consumption behavior of the last 3 months before collection. 23 The analytical limits of the method enable the detection of very low concentration in the hair samples. However, strong cosmetic treatments like bleaching can degrade the incorporated substances.…”
Section: Hair Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Medications for opioid use disorder (MOUD)—such as methadone, buprenorphine, or buprenorphine-naloxone—curb opioid cravings and decrease overdose events [ 4 ]. MOUD treatment programs have become a key public health strategy in combatting the opioid epidemic [ 5 , 6 ], particularly during the COVID-19 pandemic [ 7 ].…”
Section: Introductionmentioning
confidence: 99%